How is entrepreneurship as generic and professional competences diverse? Some reflections on the evaluations of university students' generic competences (students of education and bioeconomics) - Slišāne, Agnese; Lāma, Gatis; Rubene, Zanda (Frontiers in Education, 2022)
Generic competences have an interdisciplinary nature, which indicates their usability in different disciplines, situations, and contexts in the performance of different tasks. Generic competencies are thus considered from two perspectives, daily life and professional activity, that are equally important, implying that generic competences are necessary for individuals to successfully adapt to change and live meaningful and productive lives. Entrepreneurship competences can be observed from two perspectives: generic competencies viewed from the perspective of the individual's personal experience and professional competencies viewed from the perspective of the individual's professional experience. In this article, it will be observed from both perspectives to see its performance in diverse contexts and to clarify distinctions between these contexts. The present study aimed to shed light on how specific university study disciplines with a professional focus (educational sciences and bioeconomics) support the development of a specific generic competence (entrepreneurship competencies). The Specific Research Questions of This Article Are: (1) What Entrepreneurship Competences Emerge Among Latvian Bioeconomics and Educational Science Students? (2) How Do Entrepreneurship Competences Differ Between Bioeconomics and Educational Science Students? (3) How Are Entrepreneurship Competences Correlated With Each Other? Data for the study were gathered by using the online survey platform QuestionPro. The questionnaire was filled in by 135 students, of whom 82 were from the field of educational sciences and 53 from the field of bioeconomics. The study presents a comparison of entrepreneurship competence's self-assessments of bachelor's, master's, and doctoral students of bioeconomics and educational sciences. Despite the fact that entrepreneurship is more linked to economics, the results show that, in two out of three main areas of entrepreneurship competences, students of educational sciences self-assessed their entrepreneurship competences as higher than students of bioeconomics.